2016
DOI: 10.1111/bpa.12351
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Mechanisms of Disease Course Variability in ALS from Mutant SOD1 Mouse Models

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a heterogeneous disease in terms of progression rate and survival. This is probably one of the reasons for the failure of many clinical trials and the lack of effective therapies. Similar variability is also seen in SOD1(G93A) mouse models based on their genetic background. For example, when the SOD1(G93A) transgene is expressed in C57BL6 background the phenotype is mild with slower disease progression than in the 129Sv mice expressing the same amount of transgene but sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 105 publications
3
55
0
Order By: Relevance
“…Most human SOD1 mutation carriers likewise had the inflammatory PNS pattern that is found in SOD1 mice. Peripheral nervous system inflammation is found predominantly in the mutant SOD1 mice strain C57‐SOD1(G93A), which reveals a more benign disease course including a delayed onset of symptoms, slow disease progression, and prolonged survival . For humans, there are virtually no data on the significance of PNS inflammation in ALS, with the exception of 1 report of lower hazard of death in participants with, compared to those without, sural nerve inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…Most human SOD1 mutation carriers likewise had the inflammatory PNS pattern that is found in SOD1 mice. Peripheral nervous system inflammation is found predominantly in the mutant SOD1 mice strain C57‐SOD1(G93A), which reveals a more benign disease course including a delayed onset of symptoms, slow disease progression, and prolonged survival . For humans, there are virtually no data on the significance of PNS inflammation in ALS, with the exception of 1 report of lower hazard of death in participants with, compared to those without, sural nerve inflammation .…”
Section: Discussionmentioning
confidence: 99%
“…A mutant SOD1 G93A mouse model of ALS on a 129Sv genetic background has an earlier age of onset than a SOD1 G93A mouse model on a C57BL6 genetic background despite an equal expression of the mutant protein (Marino et al, 2015). These mice have also faster disease progression and an intrinsic marked down-regulation of specific pathways involved in mitochondrial function and protein quality control (Nardo et al, 2013(Nardo et al, , 2016Marino et al, 2015). Conversely, ApoE2 polymorphism and lower EPHA4 expression have been correlated with delayed age of onset in ALS patients (Li et al, 2004;Van Hoecke et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that axonal degeneration rather than motor neuron loss is the cause of disease acceleration and that the immune system made a major contribution to the variability of the disease course. In particular, the upregulation of immune molecules such as complement and MHC class I molecules may be responsible for more efficient axonal preservation in transgenic mice with slowly progressing MND [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Progression of the disease is inherently heterogeneous and influenced by clinical, demographic, and genetic traits [8]. In animal models the activation of the immune response has been found to have a protective role [9]. …”
Section: Introductionmentioning
confidence: 99%